IMPLEMENTASI PEMBELAJARAN LINTAS MINAT MATA PELAJARAN EKONOMI SAINS SMA NEGERI 1 SUNGAI AMBAWANG - Wahyudi, Wahyudi; Ulfah, Maria; Achmadi, Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the difficulties faced by students in learning across the interests of economic subjects. The focus of the study consisted of teachers using or implementing learning across the interests of economic subjects SMA Negeri 1 Ambawang River class X Science with the principles of the principles that exist as a basic reference among others, of learners are told to learners to find out, From teachers as the only source of learning to learning based on various learning resources, From learning verbalitas meneuju applicative skills, Learning that applies values by giving exemplary. The research method is descriptive with survey research form. The sample of this study amounted to six people and subject teachers. Data collection techniques are Observation, Interview / interview, Documentation and triangulation / combination, while the data collection tool is Checklist, interview guide. The results of the study show the implementation of learning across the economic interest in the class of ten Science, the difficulties faced by students in learning across the interests of economic subjects, what efforts do economic teachers in learning across interest in economic subjects.Keywords: Implementation of learning across interests, economic subjects